Fast and Reliable Electronic Assay of a Xylella fastidiosa Single Bacterium in Infected Plants Sap. Issue 30 (28th August 2022) - Sarcina, Lucia; Macchia, Eleonora; Loconsole, Giuliana; D'Attoma, Giusy; Bollella, Paolo; Catacchio, Michele; Leonetti, Francesco; Di Franco, Cinzia; Elicio, Vito; Scamarcio, Gaetano; Palazzo, Gerardo; Boscia, Donato; et al.
Abstract: Pathogens ultra‐sensitive detection is vital for early diagnosis and provision of restraining actions and/or treatments. Among plant pathogens, Xylella fastidiosa is among the most threatening as it can infect hundreds of plant species worldwide with consequences on agriculture and the environment. An electrolyte‐gated transistor is here demonstrated to detect X. fastidiosa at a limit‐of‐quantification (LOQ) of 2 ± 1 bacteria in 0.1 mL (20 colony‐forming‐unit per mL). The assay is carried out with a millimeter‐wide gate functionalized with Xylella ‐capturing antibodies directly in saps recovered from naturally infected plants. The proposed platform is benchmarked against the quantitave polymerase chain reaction (qPCR) gold standard, whose LOQ turns out to be at least one order of magnitude higher. Furthermore, the assay selectivity is proven against the Paraburkholderia phytofirmans bacterium (negative‐control experiment). The proposed label‐free, fast (30 min), and precise (false‐negatives, false‐positives below 1%) electronic assay, lays the ground for an ultra‐high performing immunometric point‐of‐care platform potentially enabling large‐scale screening of asymptomatic plants. Abstract : An electrolyte‐gated transistor is demonstrated here to detect Xylella fastidiosa at a limit‐of‐quantification of 2 ± 1 bacteria in 0.1 mL (20 colony‐forming‐unit per mL). The proposed label‐free, fast (30 min), and precise (false‐negatives, false‐positives below 1%) electronic assay lays the ground for an ultra‐high performing immunometric point‐of‐care platform potentially enabling large‐scale screening of asymptomatic plants.